Pelatihan Literasi Keuangan bagi UMKM Rufata di Pancoran Jakarta Selatan: Upaya Menjaga Stabilitas Modal Usaha - Nurhafifah Amalina; Sumiyarti; Sri Yani Kusumastuti; Nidya Khaeruni (Dirkantara Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) often face challenges in maintaining business sustainability due to limited financial management skills. To address this issue, a Community Service Program was conducted by the Faculty of Economics and Business, Universitas Trisakti, in collaboration with MSME Rufata located at Gudang Sarinah Pancoran, South Jakarta, in May 2024. The program involved 25 MSME participants and was designed to enhance financial literacy through interactive training. The implementation methods included lectures, group discussions, question-and-answer sessions, and practice exercises covering key topics such as cash management, basic financial recording, budgeting, and strategies to safeguard business capital. Evaluation results indicated a significant improvement in participants’ understanding, as evidenced by higher post-test scores compared to pre-test results. Most participants also reported that the training was beneficial for daily business practices, particularly in applying more systematic financial records and structured budget planning. This program not only improved managerial skills but also contributed positively to business sustainability and the economic stability of the surrounding community.